Inovasi Hijau sebagai Strategi Pengembangan Usaha Kecil Mikro Syariah - St Nur Rahma; Siradjuddin Siradjuddin (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2022)
This study aims to understand, describe and analyze Green Innovation on the development of Micro Enterprises in terms of Islamic values based on the Qur'an and hadith. The research method used is library research. The results show that the green concept is in line with the basic principles of Islamic ethics, namely al-'adl (justice), istihan (preference for the better), maṣlaḥah (public needs), 'urf (habits), istiṣlāḥ (improvement) and i'tidāl (harmony). Innovation becomes ideal so that it is not only profit-oriented but also benefit-oriented and not just a low carbon emission policy or green model based on illegitimate environmental ethics. The ideal concept of sustainable development substantively presents the idea of how the Islamic economic perspective on human relations with the environment, in relation to the development of sharia micro-enterprises, so that the application of green innovation will have an impact on increasing productivity and realizing goodness for business actors and the natural environment in a sustainable manner.